2022
DOI: 10.3390/cancers14061539
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Pancreatic Metastases of Renal Cell Cancer: Genetics and Epigenetics of an Unusual Tumour Entity

Abstract: Isolated pancreatic metastases of renal cell carcinoma (isPMRCC) are a rare manifestation of metastatic renal cell carcinoma (mRCC) characterized by two peculiarities: (1). The definite or at least long-term exclusive occurrence of metastases in the pancreas and (2). an unusual low tumour aggressiveness with slow tumour progression and consecutive, good treatment results. According to current knowledge, the exclusive occurrence of pancreatic metastases is due to a highly specific and highly selective seed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 311 publications
0
18
0
Order By: Relevance
“…However, biological studies have not yet conclusively demonstrated the proclivity of renal cell carcinoma to metastasize to the pancreas exclusively. It was recently reported that isolated pancreatic metastasis of renal cell carcinoma exhibit genetic changes (lack of 9p loss, reduced-weight genome instability index, low frequency of BAP1 alterations, and a high frequency of PBRM1 loss) that are associated with low tumor aggression ( 19 ). In the present case, the blood supply to the pancreatic lesion was from the celiac artery, and that to the ectopic pancreas in the duodenum was from the superior mesenteric artery.…”
Section: Discussionmentioning
confidence: 99%
“…However, biological studies have not yet conclusively demonstrated the proclivity of renal cell carcinoma to metastasize to the pancreas exclusively. It was recently reported that isolated pancreatic metastasis of renal cell carcinoma exhibit genetic changes (lack of 9p loss, reduced-weight genome instability index, low frequency of BAP1 alterations, and a high frequency of PBRM1 loss) that are associated with low tumor aggression ( 19 ). In the present case, the blood supply to the pancreatic lesion was from the celiac artery, and that to the ectopic pancreas in the duodenum was from the superior mesenteric artery.…”
Section: Discussionmentioning
confidence: 99%
“…In terminal systemic disease tumors, pancreatic metastasis rarely occurs, in approximately 2% of surgical cases, with a corresponding poor prognosis ( 8 , 9 ). However, among patients with multi-organ site mRCC, concomitant PM presents a better prognosis compared to the cases without PM (median OS: 42 months vs. 23 months) ( 10 ). Furthermore, isPMRCC is characterized by an unusually favorable prognosis after surgical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatectomy for metastasis is not common, although RCC is the most common primary source ( 33 ). A survival benefit is associated with this subset of patients when they undergo surgery (complete oncological resection is associated with a 5-year survival rate of 75%) ( 10 ), particularly if RCC is the primary source ( 34 ). However, it has been reported that after the treatment of isPMRCC, 41.5% of patients present recurrence (125 patients among 301 patients relapsed after a 30-month interval) ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The definite or at least for a very long time exclusive occurrence of PM in RCC cannot, as initially assumed, be due to the topographic proximity of the kidney and pancreas via pre-existing lymphatic [22,66,79,84,138,154,161,177] or venous renal-portal vascular connections between the kidney and the nearby pancreas [84,295,296] or by acquired pathological tumour vessels of hyper-vascularised tumours [10,22,66,79,84,115,138,153,161,173,205]. As our working group pointed out already in 2018, the local metastasis pathway is not compatible with the following characteristics of the isPMRCC [297]: (1) The independence of the distribution of metastases in the pancreas from the side of the primary RCC [106,143,160,183,184,188,211,233,259,297,298], (2) the even distribution of isolated PM within the pancreas [299], (3) the rare occurrence (6.2% [300]) of regional LNN metastases [99,102,111,116,121,143,…”
Section: Ispmrcc and Seed And Soil Mechanismmentioning
confidence: 99%